Transmissibility of Human T-Lymphotropic Viruses through Blood Transfusion in Africa: A Public Health Challenge - Muhibi Musa Abidemi 1*, Olaniyan Mathew Foloranmi 1, Tijani Busira Adesina 2, Muhibi Mutmainah Opeyemi 3 (Sokoto Journal of Medical Laboratory Science)
Human T-lymphotropic viruses (HTLV) types 1 and 2 are retroviruses primarily transmitted through close contact with infected bodily fluids. While blood transfusion is a significant route of HTLV transmission, improved screening measures can drastically reduce this risk. This review examines the historical context of HTLV transmission through blood transfusion, the current state of screening and risk mitigation strategies, and ongoing research efforts.